Vitamin D in Lupus Patients of Childbearing Age: Are We Doing Enough? - Statache, Gianina; Brown, Sadaf (Frontiers in Reproductive Health, 2022)
Systemic lupus erythematosus patients have long been observed to suffer from vitamin D deficiency. This can be related to either environmental factors, medication or other comorbidities like a renal disease. Moreover, lupus patients have reported conception issues including ovarian failure or recurrent miscarriages. There are vast data regarding vitamin D’s ability to support the development of a healthy pregnancy and prevent complications (preeclampsia, gestational diabetes), likely through its ability to regulate both innate and adaptive immune system. Although there is an agreement in the medical world that pregnant lupus patients should be screened and receive vitamin D supplements, there are no official guidelines on screening and often the recommended doses are suboptimal. Further research is needed to look at the potential of vitamin supplementation in pregnant lupus patients.